Istri Nusyuz Dan Suami Dayyus - Lubis, Risma Handayani; Sirait, Lailatusy Syifa (Fakultas Syariah dan Hukum, 2024)
Nusyuz is defined as an act or condition of conflict with the occurrence of conflict or defiance between husband and wife in domestic life while husband dayyus is the loss of jealousy in the heart of a person to his family who commits sins so as to let them fall into great sin. A wife can be said to be nusyuz if she does not want to carry out the duties of filial piety outwardly and inwardly to her husband in terms justified by Islamic law except in the presence of a valid reason, then KHI regulates the husband's obligation to his wife is the husband as a guide to his wife and household and the existence of this rule makes a husband unable to apply dayyus to his household because if the husband becomes a dayyus then his family will not be guided to a good path. This study aims to determine the analysis of nusyuz wives and dayyus husbands in Islamic law, knowing the form and settlement in Islamic law using normative research methods. Analysis of this study used a reading approach (library research). The results of this study found a general description of nusyuz wives and dayyus husbands, namely; (1) A wife can be said to be nusyuz if she does not want to carry out the duties of filial piety outwardly and batih to her husband in terms justified by Islamic law, except for a valid reason. (2) The IHL regulates the obligations of the husband to his wife as a guide to his wife and household and the existence of this rule makes a husband unable to act dayyus towards his household. This study is expected so that the community is not blind to the existing marriage law, where a husband or father must be able to be a protector for his wife and children as article 80 paragraph 2 of the KHI and article 34 of Law Number 1 of 1974.